Comprehensive investigation on ballistic injection characteristics of GDI injector: A particular focus on injection pressure and fuel effects. (1st March 2023) - Moon, Seoksu; Faruk Atac, Omer; Bae, Gyuhan; Park, Jeonghwan
Highlights: GDI injectors are studied comprehensively in ballistic and linear injection regimes. Injection pressure and fuel effects are surveyed using a Bosch injection rate meter. More complicated and dramatic effects of injection parameters in the ballistic regime. Slower needle rising and short injection duration at high injection pressures. Longer injection delay and reduced injection mass at high fuel viscosities. Abstract: The ballistic injection occurs in the short injection pulse conditions of solenoid-actuated fuel injectors, in which the injection mass does not have a linear relationship with the coil energizing time (injection pulse duration). Sometimes, a reversal stage appears in the ballistic regime in which the injection mass temporarily decreases against the increase of injection pulse duration. Previous studies have observed these nonlinear injection characteristics but insufficient attention has been paid to what are the related mechanisms and how they appear differently based on injection parameters. Understanding these is of great importance for the advanced design and control of fuel injectors in conventional and alternative fuel engines, particularly applying the short-pulse multiple injection strategies. The current study investigates the injection pressure and fuel effects on ballistic and linear injection characteristics of a gasoline direct injection injector using a Bosch long-tube injection rate meter. In the long-pulse linear injection regime, the injection pressure effect showed a typical trend but the fuel effects appeared insignificant. However, these injection pressure and fuel effects appeared more complicated and dramatic in the ballistic regime. The increase in the injection pressure showed a slower needle rise which caused a shorter injection duration and the appearance of the reversal stage at a longer injection pulse duration. The higher fuel viscosity caused a longer injection delay, which resulted in a shorter injection duration, lower injection mass, and the appearance of the reversal stage at a longer injection pulse duration. The needle dynamics associated with the ballistic injection characteristics and their dependence on injection parameters were thoroughly discussed based on the results.